2019
DOI: 10.5194/amt-12-2423-2019
|View full text |Cite
|
Sign up to set email alerts
|

Merging of ozone profiles from SCIAMACHY, OMPS and SAGE II observations to study stratospheric ozone changes

Abstract: Abstract. This paper presents vertically and zonally resolved merged ozone time series from limb measurements of the SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY (SCIAMACHY) and the Ozone Mapping and Profiler Suite (OMPS) Limb Profiler (LP). In addition, we present the merging of the latter two data sets with zonally averaged profiles from Stratospheric Aerosol and Gas Experiment (SAGE) II. The retrieval of ozone profiles from SCIAMACHY and OMPS-LP is performed using an inversion algor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 54 publications
8
36
0
Order By: Relevance
“…The same feature was also observed by Arosio et al (2019). Enhanced ozone trends over the mid-latitude Atlantic sector are seen in both absolute and relative units, and also at lower altitudes (but the ozone trends are not statistically significant below 40 km).…”
Section: Evaluation Of Regional Ozone Trendssupporting
confidence: 77%
See 4 more Smart Citations
“…The same feature was also observed by Arosio et al (2019). Enhanced ozone trends over the mid-latitude Atlantic sector are seen in both absolute and relative units, and also at lower altitudes (but the ozone trends are not statistically significant below 40 km).…”
Section: Evaluation Of Regional Ozone Trendssupporting
confidence: 77%
“…We compared also the trends in late 2004 -2018, the common measurement period, using MEGRIDOP, only MLS data and the merged SCIAMACHY-OMPS dataset by Arosio et al (2019). We found that the spatial distributions of ozone trends are similar for the considered datasets (Figure 12, top).…”
Section: Evaluation Of Regional Ozone Trendsmentioning
confidence: 91%
See 3 more Smart Citations